Synthesis, β -catenin Translocation Capability and ALP Activation Activity of 7H-thiazolo[3,2-b]-1,2,4-triazin-7-one Derivatives - Hou, Shicheng; Xu, Henan; Hu, Jianshu; Hou, Jian; Wang, Yan; Jin, Zhe; Wan, David C.C.; Hu, Chun (Medicinal Chemistry, 2018)
Background: Osteoporosis (OP) is a common bone disease, most often diagnosed in post-menopausal women. The majority of OP treatments are focused on manipulation of the patient's hormone levels, therefore, they are associated with significant adverse effects. Objective: The study aimed to design, synthesize and evaluate the β-catenin translocation capability and the alkaline phosphatase (ALP) activation activity of 7H-thiazolo[3,2-b]-1,2,4-triazin-7-one derivatives. Method: The styrene derivatives were synthesized as raw materials, followed by oxidation and condensation reactions, in which 6-aryl-3-thioxo-3,4-dihydro-1,2,4-triazin-5(2H)-one derivatives (1) were obtained. The 3,6-diaryl-7H-thiazolo[3,2-b]-1,2,4-triazin-7-ones (2) were obtained by a condensation reaction of compound 1 with substituted phenacyl chlorides in acetic acid. The target compounds 3,6-diaryl-7H-thiazolo[3,2-b]-1,2,4-triazin-7-ones (3a-3c) were prepared by compound 2 with substituted alkyl chloride by Williamson reaction. As to 6-benzyl-3-aryl-7H-thiazolo[3,2- b]-1,2,4-triazin-7-one derivatives as the target compounds, the benzaldehyde and acetylglycine used as raw materials, followed by Erlenmeyer-Plochl reaction, condensation reaction, hydrolysis reaction, condensation reaction, 6-benzyl-3-thioxo-3,4-dihydro-1,2,4-triazin-5(2H)-one derivatives were obtained, and were converted to the target compounds 6-benzyl-3-(hydroxylaryl)-7Hthiazolo[ 3,2-b]-1,2,4-triazin-7-one derivatives (5a-5d) using reaction with substituted α-phenacyl chlorides. Finally, Williamson reaction were used to yield 6-benzyl-3-aryl-7H-thiazolo[3,2-b]- 1,2,4-triazin-7-ones as target compounds (6a-6e). The β-catenin translocation capability and the ALP activation activity were tested, and the glycogen synthase kinase-3 (GSK-3) inhibition was simulated by molecular docking. Results: Fourteen 7H-thiazolo[3,2-b]-1,2,4-triazin-7-one derivatives were synthesized and characterized by mass spectra, proton NMR and infrared spectra, the β-catenin translocation capability and the ALP activation activities of the target compounds were tested and calculated. The EC50 value of the ALP activation activity of 6-(4-chlorobenzyl)-3-4-[(2-dimethylamino)-2- oxoethoxy]phenyl-7H-thiazolo[3,2-b]-1,2,4-triazin-7-one (6b) was 11.283 μM. The molecular docking results have showed that the target compounds would be GSK-3 inhibitors. Conclusion: Based on the results of the biological activity test, the target compounds have exhibited the β-catenin translocation capability and the ALP activation activity.
Keywords: triazine